Increased levels of palmitoylethanolamide and other bioactive lipid mediators and enhanced local mast cell proliferation in canine atopic dermatitis - Abramo, Francesca (BioMed Central, 2014)
BACKGROUND: Despite the precise pathogenesis of atopic dermatitis (AD) is unknown, an immune dysregulation that causes Th2-predominant inflammation and an intrinsic defect in skin barrier function are currently the two major hypotheses, according to the so-called outside-inside-outside model. Mast cells (MCs) are involved in AD both by releasing Th2 polarizing cytokines and generating pruritus symptoms through release of histamine and tryptase. A link between MCs and skin barrier defects was recently uncovered, with histamine being found to profoundly contribute to the skin barrier defects. Palmitoylethanolamide and related lipid mediators are endogenous bioactive compounds, considered to play a protective homeostatic role in many tissues: evidence collected so far shows that the anti-inflammatory effect of palmitoylethanolamide depends on the down-modulation of MC degranulation. Based on this background, the purpose of the present study was twofold: (a) to determine if the endogenous levels of palmitoylethanolamide and other bioactive lipid mediators are changed in the skin of AD dogs compared to healthy animals; (b) to examine if MC number is increased in the skin of AD dogs and, if so, whether it depends on MC in-situ proliferation. RESULTS: The amount of lipid extract expressed as percent of biopsy tissue weight was significantly reduced in AD skin while the levels of all analyzed bioactive lipid mediators were significantly elevated, with palmitoylethanolamide showing the highest increase. In dogs with AD, the number of MCs was significantly increased in both the subepidermal and the perifollicular compartments and their granule content was significantly decreased in the latter. Also, in situ proliferation of MCs was documented. CONCLUSIONS: The levels of palmitoylethanolamide and other bioactive lipid mediators were shown to increase in AD skin compared to healthy samples, leading to the hypothesis that they may be part of the body’s innate mechanisms to maintain cellular homeostasis when faced with AD-related inflammation. In particular, the increase may be considered a temptative response to down-regulating the observed elevation in the number, functionality and proliferative state of MCs in the skin of AD dogs. Further studies are warranted to confirm the hypothesis.